1998
DOI: 10.3141/1641-16
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Alternative Fuel Vehicle Choice in the Continental United States

Abstract: This paper describes the ongoing investigation into the determinants of alternative fiel vehicle choice. A stated preference vehicle choice sumey was conducted for the 47 of continental" U.S. states, excluding California. The national survey is based OL and is an extension o~previous studies on alternative fuel vehicle choice for the State of CaMornia conducted by.the University of California's Jnstitute of Transportation Studies (UC ITS). Researchers at UC ITS have used the stated-preference national survey t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 4 publications
0
35
0
1
Order By: Relevance
“…Especially attitudinal surveys are often used in a first phase to develop the survey instrument or to obtain in-depth information about the consumers' attitudes on environmental issues. Second, research from the 80s and 90s mainly focused on the potential demand for battery EVs [13,14,24,27,38,39,54,55,79,90], while studies from the late 90s and 2000s rather address a mix of AFVs including EVs, LPG, CNG or methanol [21][22][23]33,34,42,81,87]. In line with technological developments, recent research also concentrates on HEVs [3,10,26,29,31,32,45,49,53,72], PHEVs [ 9 , 11], bi ofuels [51,68,69,80,89,91], hydrogen [2,66,74,76,86] and HFCVs [46,61,62,65].…”
Section: Evaluation Of the Retrieved Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Especially attitudinal surveys are often used in a first phase to develop the survey instrument or to obtain in-depth information about the consumers' attitudes on environmental issues. Second, research from the 80s and 90s mainly focused on the potential demand for battery EVs [13,14,24,27,38,39,54,55,79,90], while studies from the late 90s and 2000s rather address a mix of AFVs including EVs, LPG, CNG or methanol [21][22][23]33,34,42,81,87]. In line with technological developments, recent research also concentrates on HEVs [3,10,26,29,31,32,45,49,53,72], PHEVs [ 9 , 11], bi ofuels [51,68,69,80,89,91], hydrogen [2,66,74,76,86] and HFCVs [46,61,62,65].…”
Section: Evaluation Of the Retrieved Datamentioning
confidence: 99%
“…These reviewed CM studies reveal that the most critical factors for the adoption of AFVs are price characteristics (e.g., purchase price, fuel costs) [3,26,29,33,72,79], followed by performance and convenience attributes (e.g., driving range, recharging times, fuel availability) [13,14,21,24,27,29,33,42,72,79]. Although people express a willingness to pay for reduced emission levels [21,23,87], environmental benefits are consistently found to be of minor importance compared to these attributes [26,27,34,72].…”
Section: Preference Valuation Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Households own a majority of the minivans and sport utility vehicles for personal travel. An ANL survey showed that minivan-owning households are less likely to adopt new technologies readily (Tompkins et al 1998). Also, the owners of minivans (which are classified as light trucks) treat them as larger station wagons.…”
Section: Market Penetration Projectionsmentioning
confidence: 99%
“…The subgroup consists of farm products, wet corn milling, 2 soybean oil mills, chemical preparations, n.e.c. 3 , soap and detergent, and petroleum refining. These multipliers are derived from the Regional Input-Output Modeling System (RIMS II) developed by the Bureau of Economic Analysis (BEA), U.S. Department of Commerce.…”
Section: Hddv -Heavy Dutymentioning
confidence: 99%